The Effect of Project-Based Learning Models toward Science Process Skills (SPS) in Elementary School Students - Rintayati, Peduk (Journal of General Education Science, 2023)
Science Process Skills are students' key to acquiring science knowledge scientifically. However, the state of SPS in elementary school students is still low. This study aims to determine the effect of the Project-based Learning (PJBL) learning model in science learning on students' science process skills (SPS) in elementary schools. The study used a pretest-posttest control group design. The research sample was 350 fifth grade elementary school students in Surakarta City. Samples were chosen randomly. The data collection technique uses the SPS test in terms of the learning process. Data analysis was performed using the independent t-test. The research results obtained a significance value at the 95% confidence level of 0.000 <0.05 so it can be concluded that there is a difference between students in the experimental and control groups. Students who use the PJBL model have a higher SPS compared to the learning model that is usually applied in class (assignments). Research recommends that teachers be able to design PJBL learning for better student SPS.